Evaluation of total phenolic content and antibacterial activity of palygnnum minus leaves methanolic extract against food borne pathogens / Nurul Alia Farhah Mohd Zamri - Mohd Zamri, Nurul Alia Farhah (2015)
Polygonum minus, subspecies of a large medicinal genus of Polygonaceae have long provided mankind with its tremendous benefits in providing ailment for various illnesses. Despite its aromatic flavors, P. minus had been reported to possess high polyphenol content that responsible for its antibacterial and antioxidant activities. P. minus had been traditionally used to treat gastrointestinal related diseases which this property can be the answer to resolve emerging elevated multi-resistant in foodborne pathogens. This study attempts to evaluate total phenolic content and antibacterial activity of P. minus leaves methanolic extract against foodborne pathogens which are Staphylococcus aureus (ATCC 43300), Bacillus cereus (ATCC 14579), Escherechia coli (ATCC 25922) and Salmonella typhimurium (ATCC 13311). In this study, polyphenol contained in P. minus extract analyzed through Folin-Ciocalteu assay presented by 11.67±0.77 GAE/g. Screening of antibacterial activity was performed using disc diffusion method at two concentrations of P. minus extract (250mg/ml and 500mg/ml). The preliminary screening of inhibition zone depicts that the extracts were more susceptible towards gram positive bacteria contrast to gram negative bacteria. Staphylococcus aureus and Bacillus cereus were subjected to Minumum Inhibitory Concentration (MIC) using a microbroth dilution method since both bacteria showed presence of inhibition zone in the initial screening test. The most striking result is that both bacteria activity were inhibited at 31.25mg/ml P. minus extract. Whereas the Minimum Bactericidal Concentration (MBC) of P. minus methanolic extract was 3.91 mg/m!. Thus, this study proved that P. minus methanolic extract has emerged as an alternative for microbial growth inhibitor in foods and its significant tremendous total phenolic content has potential as a natural antioxidant agent.